Reading resource center activities - Post, Ritamae D. (My University, 1980)
The intent of this project was to develop a series of learning activities correlated to reading. The activities are intended to be used by students in grades two, three, and four. These reading games, techniques, and manipulative aids are directed toward reinforcement of basic reading skills, and toward making reading interesting and fun. The development and preparation of this reading resource center has been an ongoing type of activity with ideas written down and incorporated into daily teaching. Many ideas and techniques were acquired from co-workers and related literature. Games have an appeal to children. They offer interesting approaches to learning the basic skills in reading. The competition involved in many of these instructional games encourages children to put forth more effort. An enthusiastic teacher with the right attitude and good instructional games could be the key to student success. This reading resource center is available to interested teachers at Westside School, Mauston, Wisconsin.
Keywords: Educational games; Reading -- Aids and devices; Reading